2009
DOI: 10.1097/sla.0b013e3181b76d2b
|View full text |Cite
|
Sign up to set email alerts
|

One Thousand Simultaneous Pancreas-Kidney Transplants at a Single Center With 22-Year Follow-Up

Abstract: Diabetic patients with end-stage renal failure have a poor prognosis without transplantation. Transplantation with SPK provides a marked extension of the patient's life and freedom from insulin injections. Enteric drainage is currently the surgical technique of choice. SPK transplantation should be considered the treatment of choice in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
221
5
22

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(266 citation statements)
references
References 20 publications
18
221
5
22
Order By: Relevance
“…Of note, these patient survival rates were similar to those after primary pancreas transplantation4, 22, 28. Interestingly, recipients of multiple pancreas retransplantations achieved even better survival.…”
Section: Discussionsupporting
confidence: 62%
“…Of note, these patient survival rates were similar to those after primary pancreas transplantation4, 22, 28. Interestingly, recipients of multiple pancreas retransplantations achieved even better survival.…”
Section: Discussionsupporting
confidence: 62%
“…1 In fact, our 9-year survival data-93% patient, 90% kidney, and 79% pancreaswere good when compared with other published 10-year results. 1 Two important recently published papers have concluded that SPKT provides a significant extension to patient life, 1 namely 10 years longer than that of KTA from a deceased donors. 5 Our perception is that SPKT patients are really difficult to manage not only in the early period, but also in follow-up.…”
Section: Discussionsupporting
confidence: 56%
“…We observed the same causes for surgical reinterventions-infection, bleeding, and enzyme leak-as previously reported for enteric-drained patients. 1 The total length of hospital stay and intensive care residence were directly related to the presence of important complications: patients reoperated due to thrombosis, bleeding, pancreatic leak, or infection; or even patients without surgical reinterventions but who displayed relevant bleeding or infection. These patients also had an increased rate of graft loss and death.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a functioning pancreas graft improved survival by 20% at 8 years (Reddy KS, 2003). Patient survival is not statistically different according to the type of exocrine drainage (BD vs. ED), but quality of life is better and overall complications is less when BD is used (Sollinger HW, et al, 2009). Despite the improved survival, the most common type of death in these patients is death with a functioning graft and cardiovascular morbidity remains a major contributor to patient outcome in these patients (Sollinger HW, et al, 2009 (Sollinger et al, 2009).…”
Section: Long Term Results Of Pancreas Transplantationmentioning
confidence: 92%